2022
DOI: 10.1021/acsanm.2c01639
|View full text |Cite
|
Sign up to set email alerts
|

Role of ZnO in ZnO Nanoflake/Ti3C2 MXene Composites in Photocatalytic and Electrocatalytic Hydrogen Evolution

Abstract: Herein, we report a simple hydrothermal synthesis of ZnO-Ti3C2 MXene nanocomposites with a varying wt % of ZnO to exploit the synergistic effect of 2D layer structured Ti3C2 and semiconductor ZnO for photocatalysis and electrocatalysis applications. A systematic study on the efficiency of ZnO-Ti3C2 nanocomposites toward the degradation of organic pollutants (dyes and pharmaceuticals) and the hydrogen evolution reaction (HER) is demonstrated. Among the developed nanohybrid catalysts, the ZnO-Ti3C2 composite wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 68 publications
0
20
0
Order By: Relevance
“…Two peaks appear at the binding energies of 281.6 eV and 288.8 eV, corresponding to the Ti-C bond and the C-F bond, respectively. 43,45 In addition, the O 1s XPs spectrum showed two distinct peaks at 532.2 eV and 530.3 eV (Fig. 5D), the highest peak at 530.3 eV usually represent the lattice oxygen in TiO 2 , which also indicated that TiO 2 was successfully grown in situ on Ti 3 C 2 .…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Two peaks appear at the binding energies of 281.6 eV and 288.8 eV, corresponding to the Ti-C bond and the C-F bond, respectively. 43,45 In addition, the O 1s XPs spectrum showed two distinct peaks at 532.2 eV and 530.3 eV (Fig. 5D), the highest peak at 530.3 eV usually represent the lattice oxygen in TiO 2 , which also indicated that TiO 2 was successfully grown in situ on Ti 3 C 2 .…”
Section: Resultsmentioning
confidence: 90%
“…In comparison with pure AgBr, with an increase of Ti 3 C 2 @TiO 2 content, the light absorption ability of the composites gradually increases. 45,56 The fast charge transfer properties of the prepared materials were analyzed by PL spectroscopy. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The obtained UV–vis absorbance spectra are plotted in Figure A. All these materials exhibit absorbance spectra ranging from 300 to 800 nm, where the absorbance edge appearing at 357 nm indicates the incorporation of ZnO. More importantly, decreasing the n value of GO n @ZnO from 20 to 3 gradually reduces the light absorbance of particles in the range beyond 400 nm, where GO 3 @ZnO displays the lowest absorbance. Digital photos further confirm these results and GO 3 @ZnO indeed lightens the characteristic color of GO (Figure B), making GO 3 @ZnO as the optimal filler for dental composites.…”
Section: Resultsmentioning
confidence: 99%
“…Ti 3 C 2 T x was prepared by immersing 2 g MAX powder slowly in 40 ml of an aqueous solution of 40 wt% HF acid with a magnetic stir bar in a polypropylene beaker and continuously stirring at room temperature for 24 h, as reported in our previous study. 46 The resultant solution of Ti 3 C 2 T x was centrifuged at 4000 rpm and washed several times with DI water to remove AlF 3 and excess HF acid until the pH of the solution reached nearly 7. Finally, the solution was dried overnight in a vacuum oven at 80 °C.…”
Section: Methodsmentioning
confidence: 99%